Attendance to egg clutches by male Kurixalus eiffingeri increases hatching success and decreases predation by invasive slugs (Parmarion martensi) in Taiwan. (18th November 2018) - Chuang, Ming‐Feng; Borzée, Amaël; Kam, Yeong‐Choy
Abstract: Invasive species have a significant impact on amphibians, and most notably Chytrid fungi together with a few vertebrates. However, invasive terrestrial invertebrates are seldomly demonstrated to have a negative effect on their host environment, and few studies investigated the behavioural interactions between invasive and local species, limiting our knowledge of the adaptive response adopted by local organisms. These responses include whether parenting animals recognize predators as threats to their offspring and whether parental care is adequately corrected. Here, through manipulative experiments on a population of phytotelm‐breeder Kurixalus eiffingeri in central Taiwan, we demonstrated the positive effects of parental care against predation by the invasive slug Parmarion martensi, and against mould infection. Treatment groups, in the absence of caring males, displayed a higher rate of predation by slugs and mould infections. The presence of the caring males was linked to an increase in hatching success in control groups, suggesting hydration by the males, while skin peptides may be the factor limiting mould infection. We recommend further research on the impact of the invasive but widespread P. martensi on amphibian populations.